ANALISIS PEMBENTUKAN NILAI MORAL PADA ANAK KELOMPOK B MELALUI BUKU CERITA BIG BOOK DI RA. RAUDLATUL ULUM TIGASAN KULON LECES - Kulsum, Umi; Eka Dheasari, Agustiarini (Al-ATHFAL: Jurnal Pendidikan Anak, 2024)
This type of research uses descriptive research with a qualitative research approach. A qualitative research approach is a methodical approach that will focus more on a person's experiences or even problems that are unique or not the same individually. This research was conducted at RA. Raudlatul Ulum Tigasan Kulon Leces Probolinggo, in group B. The subjects in this study were 3 informants, including 1 group B teacher and 2 students' parents. Researchers used data collection techniques consisting of observation, interviews and documentation. With the Big Book with the theme of Ani's honest and humble attitude at the RA educational institution. Raudlatul Ulum can add moral values to children who previously did not understand moral behavior. The use of Big Book media with the theme of Ani's honest and humble attitude is packaged according to the needs of RA children. Raudlatul Ulum which is in Tigasan Kulon village which does not yet have Big Book media to help in forming moral values in children. Keywords: Early Childhood, Moral Values, Big book